Teknologi E-commerce dan Pengalaman Konsumen - Dera Thorfiani; Senny Handayani Suarsa; Bheben Oscar (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
This study aims to determine the descriptive analysis of each variable: e-commerce technology, independent variables; customer experience, the dependent variable; and e-commerce platform; the intervening variables are then analyzed how the direct or indirect influence of the independent variables, e-commerce technology, on the dependent variable, consumer experience, when using the e-commerce platform as an intervening variable. The quantitative method is used in this study. Based on the results of factor analysis and Structural Equation Modeling (SEM) data processing, using SPSS 23 and SMART-PLS software, the results are: 1) e-commerce technology variables indirectly have a positive and significant effect on customer experience when accessing the e-commerce platform, 2) the e-commerce technology variable has a positive and significant direct effect on customer experience. The area in this study is still limited because it merely covers Bandung Raya and is not specific for the assessment of the e-commerce platform used. For future research, the scope of research can be expanded, and the e-commerce platform used can be more specific to certain platforms so that more detailed results can be obtained